Analisis Kemampuan Membaca Pemahaman Siswa Berdasarkan Taksonomi Bloom Melalui Soal Teks Nonfiksi di Kelas V - Azhari, Farkhani; Iswara, Prana Dwija; Gusrayani, Diah (Jurnal Pena Ilmiah, 2021)
This study aims to determine how the level of students’ reading comprehension skills measured by Anderson revised BloomTaxonomy theory, difficulties faced by students, and solutions to these difficulties. The methode of this study is Descriptive Qualitative. Instrument of the study made by researcher and has been validated, that is : 2time test, questionnaire and interview. Subject of this study are student grade V in Kejaksan Elementry Schoold 2020/2021 academic. Concluded that reading skills the respond contence of the reading text on remember till understanding level included in really good cathegory with 86 score of remembering and 86,5 of understanding, on the applying level enough upper limit with 74,7 score and analizing till creating student have difficulty reading comprehension. The solutions from the these difficulties increasing the interest of reading, often read dictionary, give the direction how to find main sentence and main idea, also add illustration on the reading text.